2011
DOI: 10.17673/vestnik.2011.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Intelligent Urbanism as the Conceptual Basis of Foreign Town Planning

Abstract: Ключевые слова : градостроительство, развитие, пра-вила, природный баланс, социальное взаимодействие, эффек-тивность

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The analysis showed that the scope of the general plan of city development does not allow us to consider the questions of environmental arrangement, however, the quality of the material and spatial environment, the preservation and evolution of its value-oriented environment, its architectural and landscape composition, its decoration and lighting design and other characteristics accounting for its performance become the object of town planning [9,10,11]. Town planning as a process of imposing restrictions (regulations) on the use of city areas and the property within each of the areas of the considered urban environment is enshrined in the documents on city zoning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that the scope of the general plan of city development does not allow us to consider the questions of environmental arrangement, however, the quality of the material and spatial environment, the preservation and evolution of its value-oriented environment, its architectural and landscape composition, its decoration and lighting design and other characteristics accounting for its performance become the object of town planning [9,10,11]. Town planning as a process of imposing restrictions (regulations) on the use of city areas and the property within each of the areas of the considered urban environment is enshrined in the documents on city zoning.…”
Section: Resultsmentioning
confidence: 99%
“…This is an urgent problem of creating a comfortable environment where the daily life of urban residents flows, whose share is 3/4 of the total country population. Ultimately, we are talking about the level and quality of their life [9,10].…”
Section: Territory Including Density and Parameters Of Territory Devementioning
confidence: 99%
“…For example, over the past decade, dozens of residential complexes have been built and continue to be built in the territory of the city of Samara: Koshelev project has increased the built-up area of the city territory by 130 hectares, Novaya Samara residential area in Krasnoglinsky district of the city occupies about 58 hectares, Southern City project has expanded the urban development in the southern part of the city by more than 1000 hectares. Such area expansion results from the increase in the number of city residents and their need to obtain comfortable housing with necessary utility systems and social infrastructure [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%